Common stock repurchases and market signalling - Vermaelen, Theo (Journal of Financial Economics, 1981)
This paper examines the pricing behavior of securities of firms which repurchase their own shares. The results are consistent with a market in which investors price securities such that expected arbitrage profits are precluded. The results are also consistent with the hypothesis that firms offer premia for their own shares mainly in order to signal positive information, and that the market uses the premium, the target fraction and the fraction of insider holdings as signals in order to price securities around the announcement date. The observation that repurchases via tender offer are followed by abnormal increases in earnings per share and that mainly small firms engage in repurchase tender offers, provides further support for the signalling hypothesis.